Micropropagation of environmental stress tolerant local potato (Solanum tuberosum L.) varieties of Bangladesh - Parveen, Fazlima; Khatun, Mahmuda; Islam, Aparna (© 2014 Bangladesh Association for Plant Tissue, 2016)
This article was published in the Journal of Plant Tissue Culture and Biotechnology [© 2014 Plant Tissue Culture and Biotechnology] and the definite version is available at : http://dx.doi.org/110.3329/ptcb.v24i1.19218 The Journal's website is at:http://www.banglajol.info/index.php/PTCB/article/view/19218